Efficacy and safety of angiogenesis inhibitors in advanced gastric cancer: a systematic review and meta-analysis - Yu, Jing (J Hematol Oncol, 2016)
Monoclonal antibodies and small molecule tyrosine kinase inhibitors (TKIs) directed against the vascular endothelial growth factor (VEGF) or its receptors have been investigated in several studies for the treatment of advanced gastric cancer (GC). In the present study, we aimed to evaluate the efficacy and safety of angiogenesis inhibitors in advanced GC. We searched published randomized controlled trials (RCTs) comparing angiogenesis inhibitors with non-angiogenesis inhibitors for the treatment of GC. MEDLINE, EMBASE, and the Cochrane Controlled Trials Register were searched. The extracted data on progression-free survival (PFS) and overall survival (OS) were measured in terms of hazard ratios (HR) and corresponding 95 % confidence intervals (CIs). In addition, risk ratios (RR) and corresponding 95 % CIs were pooled for objective response rate (ORR), disease control rate (DCR), and risk of adverse events (AEs). Ten RCTs involving 2786 patients were included. Compared with non-angiogenesis inhibitor-containing regimens, angiogenesis inhibitor-containing regimens resulted in a significant improvement in OS (HR 0.80, 95 % CI 0.69–0.93, P = 0.004), prolonged PFS (HR 0.66, 95 % CI 0.51–0.86, P = 0.002), and superior ORR (RR 1.34, 95 % CI 1.09–1.65, P = 0.005) and DCR (RR 1.37, 95 % CI 1.17–1.61, P = 0.0001). Angiogenesis inhibitors were associated with a greater number of AEs, but most of these were predictable and manageable. However, hand-foot syndrome, diarrhea, and gastrointestinal (GI) perforation were significantly increased in patients treated with angiogenesis inhibitors. In summary, angiogenesis inhibitor-containing regimens were superior to non-angiogenesis inhibitor-containing regimens in terms of OS, PFS, RR, and DCR in patients with advanced GC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13045-016-0340-8) contains supplementary material, which is available to authorized users.